Respuesta :
Answer:
f = xy²-2x² satisfies that F = ∇f.
Step-by-step explanation:
F(x,y) = (y² - 4x) i + 2xy j
We want f(x,y) such that
[tex]f_x(x,y) = y^2 -4x\\f_y(x,y) = 2xy[/tex]
Lets find a primitive of y²-4x respect to the variable x. We need to think y (and y²) as constants here, so a primitive of y² would be xy² the same way that a primitive of k is xk (because we treat y² as constant). A primitive of x is x²/2, thus a primitive of 4x is 2x². Thus, a primitive of y²-4x is xy² - 2x². We can obtain any other primitive by summing a constant, however since we treated y as constant, then we have that
[tex]f(x,y) = xy^2 - 2x^2 + c(y)[/tex]
where c(y) only depends on y (thus, it is constant repsect with x).
We will derivate the expression in terms of y to obtain information about c(y)
[tex]2xy = f_y(x,y) = \frac{d}{dy} (xy^2 - 2x^2 + c(y) ) = 2xy -0 + \frac{d}{dy} c(y) = 2xy + \frac{d}{dy} c(y)[/tex]
Thus, [tex] \frac{d}{dy} [/tex] is constant. We can take f(x,y) = xy²-2x². This function f satisfies that F = ∇f.
The equation f = xy²-2x² satisfies that F = ∇f.
Calculations and Parameters:
F(x,y) = (y² - 4x) i + 2xy j
We want f(x,y) such that:
[tex]f_x(x,y) = y^2 - 4x\\f_y(x,y) = 2xy[/tex]
Next, we would have to find a primitive of y²-4x with respect to the variable x.
We would have to take y (and y²) as constants so the primitives of y² would be xy² the same.
Hence, a primitive of x is x²/2, thus a primitive of 4x is 2x². Thus, a primitive of y²-4x is xy² - 2x²
[tex]f(x,y) = xy^2 - 2x^2 + c(y)[/tex]
After differentiation,
[tex]2xy + d/dy.c(y)[/tex]
Thus, [tex]d/dy[/tex] is a constant and we can take f(x,y) = xy²-2x².
This function f satisfies that F = ∇f.
Read more about vector fields here:
https://brainly.com/question/14241484